Peran Interaksi Sosial Dalam Meningkatkan Kesejahteraan Anak Usia Dini - Alya Tulhasanah; Taopik Rahman; Risbon Siantur (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the role of social interaction in enhancing the well-being of early childhood. Child well-being includes social, emotional, and psychological aspects that are crucial for child development. Social interaction is a key factor influencing a child's ability to communicate, cooperate, and manage emotions. This study uses a qualitative approach with a literature review method by analyzing relevant sources. The results indicate that positive social interaction with peers, parents, and teachers can improve children's social skills and overall well-being. Supportive environments also help children develop self-confidence and adapt effectively to their surroundings. Therefore, the role of parents and educators is essential in creating an environment that supports children's development. Additionally, structured learning methods, such as Beyond Centers and Circle Time, have been shown to enhance social interaction among children in educational settings